A Comprehensive Analysis of Dermatological Manifestations in Lower Limb Para-Athletes - Aabedi, Andre; Wang, Vera; Agrawal, Devendra K. (Archives of Clinical and Medical Case Reports, 2026)
In this article, a critical evaluation of current evidence is presented on the prevalence, mechanisms, prevention, and management of sportrelated skin complications in amputee athletes using lower limb prostheses, highlighting emerging technologies aimed at improving skin health and athletic performance. Skin complications were highly prevalent, affecting 34%-77% of lower limb prosthesis users, with even greater frequency among athletes. The most common conditions included maceration, friction blisters, pressure ulcers, contact dermatitis, verrucous and epidermal hyperplasia, and bacterial or fungal infections. Key risk factors encompassed poor prosthetic fit, elevated activity levels, increased perspiration, prolonged wear, inadequate hygiene, and hot or humid environments. Mechanical loading and shear stress at the socket–skin interface, compounded by moisture and heat retention, were central pathophysiologic drivers. Prevention and management strategies emphasize meticulous prosthetic fitting, consistent hygiene practices, routine skin inspection, and prompt intervention for early lesions. Multidisciplinary collaboration among dermatologists, prosthetists, and rehabilitation specialists improves detection and management outcomes. Recent innovations including vented liners, temperature-regulating materials, antimicrobial coatings, and sensor-based “smart prosthetics” show promise in reducing friction, heat, and infection risk, though evidence in athletic populations remains limited. Cutaneous complications in amputee athletes are common, multifactorial, and preventable. Optimal prosthetic fit, athlete education, and coordinated interdisciplinary care are essential for minimizing morbidity and maintaining athletic participation. Technological advancements such as real-time pressure and temperature monitoring, antimicrobial materials, and adaptive socket systems may transform prevention strategies, but further sport-specific, longitudinal research is required to validate their clinical impact and guide evidencebased practice.